2016
DOI: 10.3945/ajcn.115.129064
|View full text |Cite
|
Sign up to set email alerts
|

Empty calories and phantom fullness: a randomized trial studying the relative effects of energy density and viscosity on gastric emptying determined by MRI and satiety

Abstract: Our results show that increasing the viscosity is less effective than increasing the energy density in slowing gastric emptying. However, the viscosity is more important to increase the perceived fullness. These results underscore the lack of the satiating efficiency of empty calories in quickly ingested drinks such as sodas. The increase in perceived fullness that is due solely to the increased viscosity, which is a phenomenon that we refer to as phantom fullness, may be useful in lowering energy intake. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 37 publications
1
64
2
Order By: Relevance
“…Eating 'attentively' appears to have the opposite effect (75), and food properties like viscosity can increase perceived fullness for otherwise similar foods [76]. Despite its importance, the process by which interoceptive signals are integrated remains unclear.…”
Section: How the Life-long Learning Process Contributes To Food Selecmentioning
confidence: 99%
“…Eating 'attentively' appears to have the opposite effect (75), and food properties like viscosity can increase perceived fullness for otherwise similar foods [76]. Despite its importance, the process by which interoceptive signals are integrated remains unclear.…”
Section: How the Life-long Learning Process Contributes To Food Selecmentioning
confidence: 99%
“…Camps et al . () investigated the satiating effect of viscous fibres using MRI to determine gastric emptying time. They demonstrated that fibres do not cause fullness in the stomach, but still increase subjective ratings of fullness.…”
Section: Discussionmentioning
confidence: 98%
“…Even though the higher-ED and lower-ED milks were not rated differently in liking and preference, the children may have responded to differences in sensory properties such as viscosity or creaminess (Bakke, Shehan, & Hayes, 2016; Zahn, Hoppert, Ullrich, & Rohm, 2013), which have been shown to influence satiety and fullness (Mattes & Rothacker, 2001; Zijlstra, Mars, de Wijk, Westerterp-Plantenga, & de Graaf, 2008, Camps, et al, 2016). Sensory characteristics may play a more critical role in studies of satiation, such as the present one, than in studies of satiety (Camps, et al, 2016). Alternatively, the differential response to the lower-ED and higher-ED types of milk may be explained by other mechanisms, such as differences in gastric distension and associated physiological responses of appetite-regulating hormones (Degen et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the differential response to the lower-ED and higher-ED types of milk may be explained by other mechanisms, such as differences in gastric distension and associated physiological responses of appetite-regulating hormones (Degen et al, 2006). For example, a recent study showed that both the energy density and viscosity of a dairy-based shake influenced gastric emptying (Camps, et al, 2016). The present study is the first to demonstrate that children adjust their intake to account for variations in milk ED within a meal; thus, determining the mechanisms behind this response, such as sensory properties, warrants future research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation